RESPON MASYARAKAT TERHADAP KEGIATAN POSYANDU MUTIARA HATI DI KELURAHAN BUKIT DATUK KECAMATAN DUMAI BARAT KOTA DUMAI - ANDRI BANGUN P SIMATUPANG (Welfare StatE, 2013)
Study of the society responses to the activities of the Posyandu Mutiara Hati Bukit Datuk District, Sub-District Of West Dumai, Dumai City is to examine the response of society of activities in the Posyandu Mutiara Hati Bukit Datuk District, Sub-District Of West Dumai, Dumai City The research. Type of this study is descriptive study that held in the Posyandu Mutiara Hati Bukit Datuk District, Sub-District Of West Dumai, Dumai City. Population selected in this study are each family who has baby below 5 years and ever gone to Posyandu Mutiara Hati Bukit Datuk District, Sub-District Of West Dumai, Dumai City. All of them are 127 family with 20 % sampling of population number is 25 family. For knowing the responses of society, likert scale is used as a sampling technic. Based on this study, responses those have been known from perception, behavior, and participation, so 0.792 is obtained as value. This result concludes that society responses to Posyandu Mutiara Hati activities are positive. Nevertheless, activities of posyandu are not absolute answer of infectious diseases and hazardous viruses. People that have followed the activities of posyandu are expected to keep cleanness and give good and healthy dietary pattern to children so the children can grow up good and healthy. Also, the expectation is for giving more participation on each activities of posyandu to get maximal result. Keywords: responses, posyandu, and activities of posyandu